O ensino do gênero textual crônica como estratégia de produção escrita - SANCHES, Diego Soares (2023)
The theme of this article is “The Teaching of the Chronic Textual Genre as a Strategy for Written Production”. Its general objective is to develop written production skills in the student through the chronicle genre and specific objectives a): understand the social function of the chronicle genre; b) know the structure of the chronicle genre; and c) establish the relationship between orality and writing through the chronicle genre. The theoretical-methodological framework is based on the socio-interactionist view of Antunes (2003 and 2009), focused on written production; in the work with didactic sequence according to Dolz, Noverraz and Schneuwly (2004); in the discourse genres in the view of Marcuschi (2008; 2007) and Bakhtin (1992) and in the chronicle genre, based on Bender and Laurito (1993), Sabino (1965) and Adam (1990); on Textual Typology and National Curriculum Parameters PCN (2000), which bring proposals for language teaching based on the study of genres. It is expected, with this work, that the student knows the structure, characteristics and social function of the chronicle genre; understand the importance of appropriate language in different social contexts and produce a competent chronicle.